MANURE UNGGAS: SUPLEMEN PAKAN ALTERNATIF DAN DAMPAK TERHADAP LINGKUNGAN - Yanuartono Yanuartono; Alfarisa Nururrozi; Soedarmanto Indarjulianto; Nurman Haribowo; Hary Purnamaningsih; Slamet Raharjo (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2018)
Manure Poultry: Alternative Feed Supplements and Impacts on the EnvironmentABSTRACTThe increase in protein demand is now of serious concern as the human population is forecasted to rise to as much as 9.6 billion by 2050. The poultry industry is one of the largest and fastest growing sectors of livestock production in the world. Increased production results in increased sewage so that the impact on the emergence of environmental problems associated with increased air pollution, water, and soil. The sustainability of animal feeds is crucial in the development of livestock production systems, and feed efficiency can be improved by reusing poultry waste in livestock diets, thus diminishing the use of feed grains. There are several ways of disposing of poultry waste including burial, incineration, composting, fertilizer or source of biogas energy and feed for livestock. Poultry manure is a rich source of lignocelluloses, polysaccharides, proteins, minerals, and other biological materials. It is currently expected some problems can be overcome by utilizing poultry manure waste as an alternative feed source for livestock. This paper aims to review the negative effects of excessive chicken manure and its benefits as an alternative feed for livestock and fish.Keywords: alternative feed, livestock, pollution, poultry industry, poultry manureÂ ABSTRAKKenaikan permintaan protein menjadi perhatian serius karena populasi manusia diperkirakan akan meningkat menjadi sebanyak 9,6 miliar orang pada tahun 2050. Industri perunggasan merupakan salah satu sektor produksi ternak terbesar dan tercepat di dunia. Meningkatnya hasil produksi tersebut akan menambah jumlah limbah sehingga berdampak pada munculnya masalah lingkungan yang terkait dengan peningkatan polusi udara, air dan tanah. Ketersediaan pakan hewan secara berkesinambungan sangat penting dalam pengembangan sistem produksi ternak dan efisiensi pakan dapat ditingkatkan dengan menggunakan kembali limbah unggas sebagai bahan pakan ternak, sehingga mengurangi penggunaan biji-bijian sebagai sumber pakan. Ada beberapa metode mengurangi jumlah manure ayam termasuk penguburan, insinerasi, pengomposan, pemupukan atau sumber energi biogas dan pakan ternak. Kotoran unggas adalah sumber lignoselulosa, polisakarida, protein, mineral dan bahan biologi lainnya. Saat ini diperkirakan beberapa permasalahan bisa diatasi dengan memanfaatkan limbah manure unggas sebagai sumber pakan alternatif bagi ternak. Tulisan ini bertujuan untuk mengkaji dampak negatif dari manure ayam yang berlebihan dan manfaatnya sebagai pakan alternatif untuk ternak dan ikan.Kata Kunci: industri perunggasan, manure ayam, pakan alternatif, polusi, ternak